Identification and characterization of two novel human papillomaviruses (HPVs) by overlapping PCR: HPV102 and HPV106 - Chen, Zigui (2007)
Complete genomes of HPV102 (8078 bp) and HPV106 (8035 bp) were PCR amplified and cloned from cervicovaginal cells of a 49-year-old Hispanic female with reactive changes on her Pap test and a 42-year-old Hispanic female with a Pap test diagnosis of atypical squamous cells of unknown significance (ASCUS), respectively. The nucleotide sequence similarity of the complete L1 open reading frame (ORF) determined that HPV102 and HPV106 are most closely related to HPV83 (84.1 % identity) and HPV90 (83.5 % identity), respectively, placing them in the genital HPV groups, papillomaviruses species α3 and α15. HPV102 and HPV106 contain five early genes (E6, E7, E1, E2, and E4) and two late genes (L2 and L1), and both lack an E5 ORF. On the basis of phylogenetic analyses and available clinical information, these two novel HPV types expand the heterogeneity of HPVs detected in the lower genital tract.